Poster Digital Sains dalam Pembelajaran Berbasis Proyek: Analisis Keterampilan dan Persepsi Mahasiswa PIAUD - Kusayang, Titin; Pranata, Ogi Danika (UIN Sultan Maulana Hasanudin Banten, 2025)
This study examines the effectiveness of using digital science posters in project-based learning to enhance students' design and presentation skills, as well as their perceptions of this activity. A quantitative descriptive and correlational methods was applied with a total sampling of 15 students from the Introduction to Science for Early Childhood course. Data analysis showed that the average poster score was high, although the correlation between poster scores and students' perceptions of project-based learning through posters was low. This indicates that a positive perception developed regardless of variations in design and presentation skills. Findings also revealed that students tend to face challenges in self- and peer-assessment. Recommendations include improving assessment structures and introducing digital application training. The integration of interactive methods is also suggested to deepen students’ understanding of concepts and their science communication skills.